A Resource-Based View Of Small Export Firms' Social Capital In A Southeast Asian Country - Roxas , Hernan 'Banjo'; Chadee, Doren (Asian Academy of Management (AAM), 2011)
This study empirically examines the social capital that facilitates the flow of export knowledge, thereby supporting the entrepreneurial stance of small export firms. By applying the VRIO (value, rarity, inimitability and organisation of firm resources) framework to the resource-based view (RBV) of the firm, this study suggests that superior performance is a function of resources that are valuable, rare, inimitable and sufficiently organised to develop and sustain the firm's competitive advantage. This study argues that small, resource-constrained export firms in a developing economy are able to adopt entrepreneurial tactics and reap positive rates of return by exploiting their relational capital to acquire export knowledge. A survey of 175 small export firms in the Philippines was conducted, and the data were analysed using structural equation modelling. The results suggest positive relationships between the firm's social capital and export knowledge. Export knowledge is associated with entrepreneurial orientation, which then correlates with export performance.